Polycentric Regional Ocean Governance Opportunity in the Benguela Current Convention - Naidoo, Ashley; Hamukuaya, Hashali; Hara, Mafaniso; Mngxe, Yamkela; Raakjær, Jesper (Frontiers in Marine Science, 2021)
The Benguela Current Convention (BCC) has been operational for a decade and has emerged from the precursor natural and fisheries science large marine ecosystem programs. This regional ocean governance institution emerged indigenously as an intergovernmental working arrangement across the Republics of Angola, Namibia, and South Africa. The Convention has been described as a Centralized Authority mode of regional ocean governance. This paper explores this description with reference to the ecosystem-based approach to marine management. The study is focused on the level of working arrangements within the Convention and its Commission across the national and regional scales. It finds that the BCC does meet the theoretical criteria of a polycentric governance mechanism at the resolution of its operations. Polycentric ocean governance mechanisms are valued in regional ocean governance as they potentially offer greater impact through higher levels of coordination, codesign, and integration. Polycentric governance systems incorporate multiple centers of authority that operate at different scales. Existing instances and further opportunities for polycentric governance mechanisms within the working arrangements of the Convention are identified for the Southeast Atlantic.